Reformist Movement in South Asia: An Analytical Study of Ahmad Sarhandi Order in Mughal System: https://doi.org/10.5281/zenodo.17226644 - Dr. Muzaffar Ali; Dr. Saima Bashir (`, 2025)
This article examines the reformist movement of Mujaddid Ahmad Sirhindi (1564–1624) in the context of the Mughal Empire, particularly under the reigns of Akbar (1556–1605) and Jahangir (1605–1627). It explores Sirhindi’s central objectives of Sharia enforcement, spiritual revival within the Naqshbandi Sufi framework, and his attempts to guide rulers and courtiers toward Islamic governance. Drawing on evidence from the Maktubat and contemporary chronicles, the study highlights the dynamics of his interaction with Mughal authority, including both cooperation and episodes of conflict. It further analyzes the challenges his reformist agenda faced, such as Akbar’s legacy of religious syncretism, court intrigues, and the gradual decline of imperial cohesion. Finally, the article assesses Sirhindi’s lasting legacy, demonstrating how his thought shaped subsequent reformist movements, influenced Mughal orthodoxy under Aurangzeb, and contributed to the intellectual foundations of the Two-Nation Theory in modern South Asia. By situating Sirhindi within the broader religious and political currents of his time, the article underscores his historical significance as both a spiritual reformer and a political thinker. Keywords: Mujaddid Ahmad Sirhindi, Maktubat-i Imam Rabbani, Mughal Empire, Sharia enforcement, Naqshbandi Sufism, religious syncretism, South Asian reform movements, Two-Nation Theory.